The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18331/brj2016.3.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Improved lipid and biomass productivities in Chlorella vulgaris by differing the inoculation medium from the production medium

Abstract: Please cite this article as: Hamedi S., Mahdavi M.A., Gheshlaghi R. Improved lipid and biomass productivities in Chlorella vulgaris by differing inoculation medium from production medium. Biofuel Research Journal 10 (2016) HIGHLIGHTSUsing different media for inoculums preparation and microalgae production improved lipid and biomass productivities.When SH4 was selected for inoculation medium and N8 was selected for production medium, 130% increase in biomass productivity and 40% increase in lipid productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…was increased to 1.56 g/L compared to the control sample of 1.31 g/L when the concentration of P in the culture media was 1500 mg/L. Meanwhile, the findings of Hamedi et al, 2016 showed that changing the medium, compared to the standard BG11 helped increase the number of C. vulgaris cells by 52% and dry weight by 54% (Hamedi et al, 2016;Li et al, 2019).…”
Section: Cell Growth Evaluationmentioning
confidence: 92%
“…was increased to 1.56 g/L compared to the control sample of 1.31 g/L when the concentration of P in the culture media was 1500 mg/L. Meanwhile, the findings of Hamedi et al, 2016 showed that changing the medium, compared to the standard BG11 helped increase the number of C. vulgaris cells by 52% and dry weight by 54% (Hamedi et al, 2016;Li et al, 2019).…”
Section: Cell Growth Evaluationmentioning
confidence: 92%